A multi-scale modeling framework for impact damage simulation of triaxially braided composites. (July 2018) - Zhao, Zhenqiang; Dang, Haoyuan; Zhang, Chao; Yun, Gun Jin; Li, Yulong
Abstract: A multi-scale simulation framework based on finite element method is developed to model the impact failure behavior of triaxially braided composite. The model integrates micromechanical model, meso-mechanical model and macro subcell model for the purpose of determining effective properties of fiber tows, estimating effective properties of subcell components, and simulating impact failure behavior of a braided composite structure, respectively. The meso-mechanical model compares excellently with experiments for mechanical behavior of both single-layer and six-layer specimens under quasi-static loading conditions. A new meso-macro homogenization approach is proposed to estimate effective properties of subcell components with consideration of geometry continuity effect. The subcell model is validated against experiments and utilized to simulate the high-speed impact behavior of a composite panel. The results of the subcell impact model compare well with experimental failure phenomena. The presented multi-scale modeling approach demonstrates its feasibility for impact analysis and design of braided composite structures.